1990
DOI: 10.1093/eurheartj/11.suppl_d.33
|View full text |Cite
|
Sign up to set email alerts
|

ACE inhibitors in the treatment of hypertension in the older patient

Abstract: Hypertension is a major potential problem among the increasing number of older persons in the population, threatening their health and shortening their life expectancy due particularly to stroke and congestive heart failure (CHF). Controlled studies have shown that antihypertensive drug therapy reduces the incidence of severe CHF, stroke and cardiovascular mortality in the elderly. Special consideration should be given to altered drug metabolism, altered responses to drugs, and concomitant medications when pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In addition, 6 patients (3.6%) in the highdose quinapril group and 2 patients (1.2%) in the combination quinapril/amlodipine group were withdrawn from the study because of an AE. In other studies, quinapril has been demonstrated to be similarly safe and well tolerated in patients with hypertension, 27,28 and additionally has been shown to preserve renal function in patients with diabetes. 29 A secondary outcome of the ANDI study was to evaluate the effect of quinapril alone compared with quinapril and amlodipine besylate in lowering hsCRP.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, 6 patients (3.6%) in the highdose quinapril group and 2 patients (1.2%) in the combination quinapril/amlodipine group were withdrawn from the study because of an AE. In other studies, quinapril has been demonstrated to be similarly safe and well tolerated in patients with hypertension, 27,28 and additionally has been shown to preserve renal function in patients with diabetes. 29 A secondary outcome of the ANDI study was to evaluate the effect of quinapril alone compared with quinapril and amlodipine besylate in lowering hsCRP.…”
Section: Discussionmentioning
confidence: 88%
“…ACE inhibitors have been used to reduce blood pressure in animal models [12][13][14] and human hypertension. [15][16][17][18][19] In conclusion, these results suggest that hypotensive effects of SDG isolated from flaxseed is mediated through inhibition of angiotensin-converting enzyme. SDG may prove to be an alternative to other ACE inhibitors for the treatment of hypertension.…”
Section: Discussionmentioning
confidence: 97%
“…A reasonable pathophysiologic approach to the pharmacologic treatment of hypertension in the elderly would call for a drug that lowers peripheral vascular resistance without further decreasing total blood volume and total body potassium. Even though the plasma renin activity may be suppressed, ACE inhibitors have been shown to be effective in the treatment of hypertension in elderly subjects 2 . Currently, there are seven ACE inhibitors on the US market.…”
mentioning
confidence: 99%